Design of Enhanced Flyback Converter for PV Application - et. al., S.Devi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The necessity of DC converters have been rapidly increasing due to the emergence of RES based electrification. However, the converter designed so far exhibits a drawback of lower efficiency and non-compactness in size. Hence, to rectify this problem, a new topology of flyback converter for PV application. The proposed converter exhibits reduced ripple current at the input side and enhances the conversion efficiency. FLC is tailored to regulate the output voltage. Finally, efficiency of this proposed converter is verified using MATLAB. The results indicate that this projected topology can be suitable for high voltage DC applications.